PELEPASAN TINTA PADA KERTAS NCR (NO CARBON REQUIRED) BEKAS DAN KERTAS UANG MENGGUNAKAN XILANASE - Trismilah, Trismilah (Badan Pengkajian dan Penerapan Teknologi, 2011)
Recycling paper is a solution to overcome the depletion of virgin pulp from trees and reduce the impact of global warming. Deinking paper is very important in the process of recycling paper. Xylanase application of research required for deinking outworn NCR paper and paper money. Deinking enzymatic is a clean technology and produces less waste than conventional deinking (chemicals). Xylanase AQ-1 which is a crude enzyme from Bacillus sp isolates AQ-1 can work well in the deinking process on the amount of enzyme addition of 0.2% in the pulp with the conditions of pH 7 and temperature of 50oC for 120 minutes. While the recombinant xylanase AQ-1 which is the result of genetic xylanase AQ-1 grown in E. coli can work well in the deinking process on the amount of enzyme addition of 0.1% in the pulp with the conditions of pH 7 and temperature of 50oC for 60 minutes. Xylanase AQ-1 increases the degree of whiteness of green NCR paper pulp from the control (40.1) into (53.9) and pulp paper moneyof the control (50.1) into (66.6). While AQ-1 recombinant xylanase increases the degree of whiteness of green NCR paper pulp from control ( 40.1) into (52.0) pulp and paper money from the control (50.1) into (63.4). Xylanase AQ-1 and recombinant xylanase AQ-1 potential in the green NCR paper deinking and paper deinking paper money, although the money still leaves some smudges on the results because of a special polymer coating that coats the waterproof paper money proficiency level.